2012
DOI: 10.5599/jese.2012.0009
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the honeycomb-like electrodes by the regime of puslating overpotential in the second range

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Thus, it is concluded that the reason of the differences observed in the morphological structure with respect to Fe : Cu ratio may be also attributed to the increase of the hydrogen evolution reaction with increasing Fe ion concentration in the electrolyte. In recent studies, the changes of surface morphology of metal films produced by electrodeposition technique at different growth conditions have been also related to the amount of hydrogen evolution reaction [29][30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is concluded that the reason of the differences observed in the morphological structure with respect to Fe : Cu ratio may be also attributed to the increase of the hydrogen evolution reaction with increasing Fe ion concentration in the electrolyte. In recent studies, the changes of surface morphology of metal films produced by electrodeposition technique at different growth conditions have been also related to the amount of hydrogen evolution reaction [29][30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…The electrodeposition technique is a very suitable way to obtain copper of desired characteristics suitable for application in above mentioned purposes [4]. Copper is possible to obtain in various morphological forms starting from compact to powdered forms by the easy selection of parameters and regimes of the electrodeposition [4][5][6]. The technologically important Cu electrodeposition processes include electroplating with a high aspect ratio [7,8], formation of functional thin films and coatings, and creation of nanoparticles and powders [4,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%